Application potential of wheat bran cellulose nanofibers as Pickering emulsion stabilizers and stabilization mechanisms - Jiawu Wu; Yang Gao; Huifang Shen; Song Yan; Rui Zhao; Fei Wang; Xinting Shen; Zhebin Li; Xinmiao Yao; Yao Wang (Food Chemistry: X)
In this paper, cellulose nanofibers (CNF) were prepared from wheat bran (WB) and the structure of CNF was determined. Fourier transform infrared spectra and X-ray diffractograms showed the groups such as hydroxyl and carboxyl groups and cellulose type 1 structure possessed by CNF, respectively. Scanning electron microscopy exhibited that CNF was filamentous and intertwined. In addition, Pickering emulsions were prepared using CNF and the physicochemical properties of the emulsions were characterized. The results showed that CNF was able to increase the zeta potential and viscosity of the emulsions, thus improving the stability of the emulsions. Moreover, CNF formed a physical barrier by adsorbing at the oil-water interface and near the oil droplets and CNF dispersed in the aqueous phase formed a network structure to restrict the movement of oil droplets, thus improving the stability of the emulsions. These findings may provide some new insights for the potential applications of WB.